Postoperative adjuvant immunotherapy for pathological stage II–IVa esophageal squamous cell carcinoma after radical surgery does not improve disease-free recurrence rates - Xie, Xihao; Zhang, Hai; He, Haiquan; Wu, Bomeng; Chen, Ying; Lin, Wanli; Feng, Qingyi; Chen, Qunqing (Frontiers in Medicine, 2024)
Background/objectivesPostoperative adjuvant therapy for esophageal squamous cell carcinoma (ESCC) primarily includes chemotherapy and chemoradiotherapy. The survival benefits of postoperative adjuvant therapy for R0-resected ESCC remain controversial. Immunotherapy is being gradually applied perioperatively for esophageal cancer, but the efficacy of postoperative immunotherapy in ESCC is unclear. This study aimed to evaluate the effectiveness of postoperative immunotherapy for esophageal cancer. Toward this goal, we explored the differences between postoperative immunotherapy combined with chemotherapy and postoperative adjuvant chemotherapy alone.MethodsThis retrospective study evaluated patients who underwent radical surgery for esophageal cancer at Gaozhou People’s Hospital between January 2020 and August 2022 and received postoperative adjuvant therapy. Patients were divided into two groups according to the adjuvant treatment regimens: postoperative adjuvant chemotherapy (aCT) and postoperative adjuvant immunotherapy combined with chemotherapy (aICT) groups. Data on baseline characteristics, surgical-related indicators, adverse event rates during adjuvant therapy, and 2-year postoperative follow-up were collected for both groups.ResultsA total of 76 patients were included: 36 and 40 patients in the aICT and aCT groups, respectively. There were no significant differences in baseline data between the two groups. During the adjuvant treatment period, the incidence of hypothyroidism was significantly higher in the aICT group than in the aCT group (25.0% vs. 2.5%, p = 0.007). During the 2-year follow-up, local and recurrence rates were 17.5 and 12.5% in the aCT group and 13.9 and 5.6% in the aICT group, respectively, showing no significant difference between the two groups (p = 0.489).ConclusionFor patients with pathologically confirmed locally advanced ESCC after surgery, postoperative immunotherapy did not confer better disease-free recurrence rates compared to postoperative adjuvant therapy. Nonetheless, with research advancements, the role of immunotherapy in the treatment of ESCC is likely to expand, offering new hope for these patients.